The Influence of Principals’ Instructional Leadership, School Culture, and Teacher Professionalism on Teacher Performance: A Quantitative Study in Junior High Schools - Sonya Diah Paramita; Senowarsito Senowarsito; Harto Nuroso (Journal of Educational Sciences, 2026)
Improving teacher performance remains a critical issue in enhancing the quality of education, particularly in strengthening school management and instructional practices. This study examined the influence of principals’ instructional leadership, school culture, and teacher professionalism on the performance of junior high school teachers in Jepara District, Jepara Regency. A quantitative approach with an ex post facto design was employed. The study involved teachers from public and private junior high schools selected through proportional random sampling. Data were collected using questionnaires and analyzed using descriptive statistics, multiple regression, and path analysis. The findings indicate that instructional leadership, school culture, teacher professionalism, and teacher performance were generally categorized as high to very high. Simultaneously, the three variables significantly influenced teacher performance. Partially, only teacher professionalism had a significant effect, while instructional leadership and school culture did not show significant direct effects. Further analysis revealed that school culture significantly influenced teacher professionalism, which in turn mediated its relationship with teacher performance. These findings suggest that teacher professionalism is the most proximal factor influencing teacher performance, while school culture functions as a contextual foundation.